Reading habits, interests and needs of rural folk towards providing library services in the social laboratory area in Pila, Laguna - Lantican, Editha S.; Picache, Ursula G.; Faderon, Rosalie B. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1985)
A study was conducted in three barrios in Pila, Laguna covered by the UPLB-SEARCA barrio development project to determine the livelihood pattern, literacy level, educational status, reading habits of the people and the materials available, informational sources used, subject matter preference and their reaction to the idea of putting up a library in the area. A 23-item interview questionnaire was used with 196 respondents, consisting of 57 household heads or husbands, 72 housewives, and 67 school-aged youth. The households were chosen at random and each was represented by a family membership of three--the husband, wife and a school-aged son or daughter. The predominant means of livelihood were farming (42 percent) and fishing (10 percent), with the rest distributed in non-agricultural vocations such as jeepney and tricycle driving.
The inhabitants showed a fairly high educational status and literacy level, 59.2 percent completed an elementary education, 29.6 percent completed a secondary education and 7.7 percent had some college education. The recreational activities indicated by the respondents are reading, listening to the radio and watching home or neighborhood television. Reading was an important recreational activity among both the adults and youngsters in the survey area. Availability of reading materials was high and every home had at least one type of reading material. Reading materials available are vernacular comics and magazines and newspapers. Frequency of reading was high, either daily or at least once during the week. The youngsters used library facilities more than the adults but this was with reference to the use of their respective school libraries.
The menfolk prefer materials that are directly related to the pursuit of their vocations and health knowledge whereas the womenfolk prefer those that relate to family affairs. The young people, the most literate group, read materials that cater to their informational, cultural and recreational needs.
The important media as personal sources of information differ among user groups. Among the menfolk, there was greater reliance on interpersonal relations with barangay leaders, technicians and friends as main sources of information. The womenfolk relied more on friends and mass media for source of information. The youngsters depended more on print materials for their informational needs.
The barrio residents in Pila have expressed a need for information. An overwhelming majority of the respondents was enthusiastic and in favor of the idea of putting up a barrio library. All three groups gave a positive response towards supporting the establishment and operation of the library.
On the basis of the findings, some of the recommendations given are that a library should be established in Pila, Laguna, as part of the rural development project; and that a choice should be made as to the type of library that can best serve the needs of a large area - either a static one using the existing but seldom-used library or a mobile library, depending on the availability of funding sources. In the interim, the existing library needs to be improved in terms of its physical facilities and size of collection. There is a need for extension type print materials in the vernacular and presented in layman's language. The inclusion of audio-visual materials and other equipment is also recommended.
Mimeographed.
Special Problem (Master of Library Science)--University of the Philippines Diliman
Keywords: Pila (Laguna) -- Social conditions; Reading interests -- Philippines -- Laguna -- Pila; Rural libraries -- Philippines -- Laguna -- Pila